Estudio de prefactibilidad para la instalación de una planta de producción de macerado en base a pisco con maracuyá (Passiflora edulis) - Chávez Cruz, Flavia Alexandra (2020)
The present study evaluates the technical, economic, social and financial viability of the installation of a Macerado production plant based on Pisco with passion fruit in Lima. This product is a differentiated alcoholic beverage that promises to quench thirst, refresh and pass a moment of pleasure and fun to the consumer The product projects an annual demand of 66,830 liters for the fifth year of the project. The target market is composed of the population belonging to Modern Lima, NSE ABC, age 18 to 50 years old, who consumes spirits and who would like to try Pisco combined with a citrus fruit such as passion fruit. The plant has an annual capacity of 66,839 liters of Macerado de Pisco with passion fruit, an area of 346m² and is located in the district of Lurín, department of Lima. The production process consists of the quality control of the inputs and materials, weighing the grapes, destemming and squeezing the grapes, pressing the must, fermenting the grape juice, distilling the Pisco, filtering the Pisco, washing and weighing the passion fruit, cut and pulp the passion fruit, mix the Pisco with the passion fruit, marinate, bottle and cover, label and fit. The total investment is S /. 1,079,349, 40% financed through a bank and 60% contributed by the shareholders. The project generates beneficial results for the shareholders, presenting a VANF of S /. 1,723,438 an IRR of 83% that is greater than the COK 11.594%, a benefit / cost ratio of 3.7 and a recovery period of 1 year and 3 months.